The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/03611981221087236
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of Compaction on Compressive Strength and Porosity Characteristics of Pervious Concrete

Abstract: An experimental study was conducted to evaluate the effect of compaction layer configuration, effort, and blow pattern on compressive strength and porosity characteristics of pervious concrete. Distinct types of compactions were applied to pervious concrete mixes with aggregate-to-cement (A/C) ratios ranging from 2.5 to 7.0. The results obtained from the experimental study revealed that three-layer compaction improved compressive resistance significantly compared with single-layer. In contrast, reduction in po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A prior study examined the A/C ratio's effect on performance and packing, which concluded that 2.65 was the theoretically ideal amount for aggregates of 12 to 18 mm [72]. An ideal A/C of roughly 4.0 was noted in another investigation [72]. This study uses a mixed design with A/C ranging in 0.5 increments from 3.0 to 5.0 to investigate this range and its possible impact on performance.…”
Section: Design and Specimen Preparationmentioning
confidence: 96%
See 1 more Smart Citation
“…A prior study examined the A/C ratio's effect on performance and packing, which concluded that 2.65 was the theoretically ideal amount for aggregates of 12 to 18 mm [72]. An ideal A/C of roughly 4.0 was noted in another investigation [72]. This study uses a mixed design with A/C ranging in 0.5 increments from 3.0 to 5.0 to investigate this range and its possible impact on performance.…”
Section: Design and Specimen Preparationmentioning
confidence: 96%
“…An essential factor in pervious concrete is the A/C ratio, which usually ranges from 3.0 to 8.0 in the literature [71]. A prior study examined the A/C ratio's effect on performance and packing, which concluded that 2.65 was the theoretically ideal amount for aggregates of 12 to 18 mm [72]. An ideal A/C of roughly 4.0 was noted in another investigation [72].…”
Section: Design and Specimen Preparationmentioning
confidence: 99%